Thermoplastic resin composition and molded article comprising same

By adding phosphonate and inorganic filler materials with specific acid values ​​to the thermoplastic resin, combined with appropriate flame retardants, the problems of discoloration and strength of existing thermoplastic resins under harsh conditions are solved, and excellent cycleability and resistance are achieved Fuelability, suitable for high temperature thin wall lightening and recycling thermoplastic resin compositions.

CN119256053APending Publication Date: 2025-01-03TEIJIN LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380041473.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-09
Filing Date
2023-05-11
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing thermoplastic resin compositions discolor and have a decrease in intensity under harsh processing conditions, and the circulation, flame retardancy and rigidity are insufficient, making it difficult to meet the needs of high-temperature thin-wall lightweighting and recycling.

Method used

Add phosphonate, inorganic filler materials and flame retardants within a specific acid range to the thermoplastic resin, combine thermoplastic resins such as polycarbonate resin and ABS resin, and use inorganic filler materials such as glass fiber and carbon fiber, and use phosphono groups. Triethyl acetate, phosphate-based compounds, etc. are used as flame retardants to optimize the composition of the resin.

Benefits of technology

The thermoplastic resin composition with discoloration and less intensity reduction under harsh conditions has excellent circulation, flame retardancy and rigidity, and is suitable for high-temperature thin-walled products and recycled products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005141518420000071
    Figure BDA0005141518420000071
  • Figure BDA0005141518420000072
    Figure BDA0005141518420000072
  • Figure BDA0005141518420000081
    Figure BDA0005141518420000081
Patent Text Reader

Abstract

Provided are: a thermoplastic resin composition which exhibits excellent cycle properties and excellent flame retardancy and rigidity, and which exhibits little discoloration and little decrease in strength even under harsh processing conditions; and a molded article comprising the thermoplastic resin composition. This thermoplastic resin composition contains 0.001-1 part by weight of (B) a phosphonate ester having an acid value of 0.01-0.30 mgKOH / g (component B) per 100 parts by weight of (A) a thermoplastic resin (component A).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a thermoplastic resin composition that has little discoloration and strength reduction during molding and a molded product made thereof. More specifically, it relates to a thermoplastic resin composition that has little discoloration and strength reduction even under severe processing conditions, has excellent recyclability, and has excellent flame retardancy and rigidity, and a molded product made thereof. Background Art

[0002] Thermoplastic resin compositions are used in a wide range of fields such as housings and parts of electrical, electronic and OA equipment, interior and exterior parts for automobiles, furniture, musical instruments, and groceries. In recent years, in order to achieve a sustainable society, in particular, it is hoped that thermoplastic resin compositions have high recyclability. On the other hand, it is well known that phosphorus compounds are used as heat stabilizers in thermoplastic resin compositions. Patent document 1 discloses the use of specific phosphorus compounds in resins composed of polycarbonate resins and polyester resins. Patent document 2 discloses the use of phosphorus compounds in combination. However, in the existing methods, the thermal stability during molding is still insufficient, especially in applications requiring thin-walled and lightweight, the molding conditions tend to be high temperature, and the number of cases where thermal stability is insufficient is increasing. In addition, the demand for recycled products has also increased, and there is an increasing demand for materials that can meet the requirements of thermoplastic resin compositions that have little discoloration or strength reduction even under harsh processing conditions, excellent recyclability, and excellent flame retardancy and rigidity.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent No. 4983427

[0006] Patent Document 2: Japanese Patent No. 5640734 Summary of the invention

[0007] An object of the present invention is to provide a thermoplastic resin composition which has little discoloration and strength reduction even under severe processing conditions, is excellent in recyclability, and is excellent in flame retardancy and rigidity, and a molded article composed of the same.

[0008] The present inventors have conducted intensive studies to achieve the above-mentioned object and have found that by adding a phosphonic acid ester having a specific acid value and an inorganic filler and / or a flame retardant to a thermoplastic resin composition, it is possible to provide a thermoplastic resin composition having less discoloration and strength reduction even under severe processing conditions, excellent recyclability, excellent flame retardancy and rigidity, and a molded article composed of the same, thereby completing the present invention.

[0009] That is, the present invention is as follows.

[0010] 1. A thermoplastic resin composition comprising 0.001 to 1 part by weight of (B) a phosphonate having an acid value of 0.01 to 0.30 mgKOH / g (component B) based on 100 parts by weight of (A) a thermoplastic resin (component A).

[0011] 2. The thermoplastic resin composition according to the above item 1, further comprising 1 to 150 parts by weight of (C) an inorganic filler (component C) based on 100 parts by weight of the component A.

[0012] 3. The thermoplastic resin composition according to the above item 1 or 2, further comprising 0.01 to 25 parts by weight of a flame retardant (component D) based on 100 parts by weight of the component A.

[0013] 4. The thermoplastic resin composition according to the above item 2 or 3, further comprising 0.05 to 3 parts by weight of (E) an anti-drip agent (component E) based on 100 parts by weight of component A.

[0014] 5. The thermoplastic resin composition according to any one of the preceding items 1 to 4, wherein component A is at least one thermoplastic resin selected from the group consisting of (A-1) polycarbonate resin (component A-1), (A-2) ABS resin (component A-2), (A-3) polyester resin (component A-3), (A-4) AS resin (component A-4), (A-5) PS resin (component A-5), and (A-6) AAS resin (component A-6).

[0015] 6. The thermoplastic resin composition according to any one of the above items 1 to 4, wherein component A is at least one thermoplastic resin selected from the group consisting of (A-1) polycarbonate resin (component A-1), (A-2) ABS resin (component A-2), and (A-3) polyester resin (component A-3).

[0016] 7. The thermoplastic resin composition according to the above item 5 or 6, wherein the content of the component A-1 is 40 to 100 parts by weight in 100 parts by weight of the component A.

[0017] 8. The thermoplastic resin composition according to any one of the above items 1 to 7, wherein the component B is triethyl phosphonoacetate.

[0018] 9. The thermoplastic resin composition according to the above item 2, wherein the component C is at least one inorganic filler selected from the group consisting of (C-1) glass fiber (component C-1), (C-2) plate-shaped glass filler (component C-2), (C-3) fibrous carbon filler (component C-3), (C-4) non-fibrous carbon filler (component C-4), and (C-5) silicate mineral (component C-5).

[0019] 10. The thermoplastic resin composition according to the above item 3, wherein the component D is at least one flame retardant selected from the group consisting of (D-1) halogenated carbonate compounds (component D-1), (D-2) phosphate compounds (component D-2), (D-3) phosphazene compounds (component D-3), (D-4) sulfonic acid metal salts (component D-4), and (D-5) organosilicon compounds (component D-5).

[0020] 11. The thermoplastic resin composition according to the above item 4, wherein the component E is polytetrafluoroethylene.

[0021] 12. A molded article, comprising the thermoplastic resin composition according to any one of 1 to 11 above. DETAILED DESCRIPTION

[0022] The present invention will be described below in detail.

[0023] <Component A: Thermoplastic resin>

[0024] The thermoplastic resin used as the component A of the present invention is a polycarbonate resin, ABS resin, polyester resin, AS resin, PS resin, AAS resin, AES resin, polyamide resin, polyolefin resin, fluorine resin, PPS resin, PEEK resin, polyarylate resin, polyacetal resin, etc., preferably at least one thermoplastic resin selected from polycarbonate resin, ABS resin, polyester resin, AS resin, PS resin and AAS resin. Moreover, the component A is more preferably at least one thermoplastic resin selected from polycarbonate resin, ABS resin and polyester resin.

[0025] The content of the polycarbonate resin is preferably 40 to 100 parts by weight based on 100 parts by weight of the component A. The content of the polycarbonate resin is more preferably 60 to 100 parts by weight based on 100 parts by weight of the component A.

[0026] <Component A-1: ​​Polycarbonate resin>

[0027] The polycarbonate resin used as component A-1 of the present invention is obtained by reacting a dihydric phenol with a carbonate precursor. As an example of a reaction method, interfacial polymerization, melt transesterification, solid phase transesterification of carbonate prepolymers and ring-opening polymerization of cyclic carbonate compounds can be cited.

[0028] Representative examples of the dihydric phenols used herein include hydroquinone, resorcinol, 4,4'-biphenol, 1,1-bis(4-hydroxyphenyl)ethane, 2,2-bis(4-hydroxyphenyl)propane (commonly known as bisphenol A), 2,2-bis(4-hydroxy-3-methylphenyl)propane, 2,2-bis(4-hydroxyphenyl)butane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 2,2-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, and 2,2-bis(4-hydroxyphenyl)-1,1-bis(4-hydroxyphenyl)-2,3-dimethylcyclohexane. The preferred dihydric phenols include bis(4-hydroxyphenyl)alkanes, ...

[0029] In the present invention, in addition to the bisphenol A-based polycarbonate resins as general-purpose polycarbonate resins, special polycarbonate resins produced using other dihydric phenols may also be used as component A-1. For example, polycarbonate resins (homopolymers or copolymers) using 4,4'-(m-phenylene diisopropylidene) diphenol (hereinafter sometimes referred to as "BPM"), 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane (hereinafter sometimes referred to as "Bis-TMC"), 9,9-bis(4-hydroxyphenyl)fluorene, and 9,9-bis(4-hydroxy-3-methylphenyl)fluorene (hereinafter sometimes referred to as "BCF") as part or all of the dihydric phenol components are suitable for applications requiring particularly strict dimensional changes and morphological stability caused by water absorption. These dihydric phenols other than BPA are preferably used in an amount of 5 mol% or more, particularly 10 mol% or more of the total dihydric phenol components constituting the polycarbonate resin. In particular, when high rigidity and better hydrolysis resistance are required, the component A constituting the resin composition is preferably a copolymerized polycarbonate resin of the following (1) to (3).

[0030] (1) A copolymer polycarbonate resin, wherein, based on 100 mol % of a dihydric phenol component constituting the polycarbonate resin, BPM is 20 to 80 mol % (more preferably 40 to 75 mol %, further preferably 45 to 65 mol %), and BCF is 20 to 80 mol % (more preferably 25 to 60 mol %, further preferably 35 to 55 mol %).

[0031] (2) A copolymer polycarbonate resin, wherein, in 100 mol % of the dihydric phenol component constituting the polycarbonate resin, BPA accounts for 10 to 95 mol % (more preferably 50 to 90 mol %, and further preferably 60 to 85 mol %), and BCF accounts for 5 to 90 mol % (more preferably 10 to 50 mol %, and further preferably 15 to 40 mol %).

[0032] (3) A copolymer polycarbonate resin, in which, based on 100 mol % of the dihydric phenol component constituting the polycarbonate resin, BPM accounts for 20 to 80 mol % (more preferably 40 to 75 mol %, and further preferably 45 to 65 mol %), and Bis-TMC accounts for 20 to 80 mol % (more preferably 25 to 60 mol %, and further preferably 35 to 55 mol %).

[0033] These special polycarbonate resins can be used alone or in combination of two or more. In addition, they can be mixed with a general bisphenol A type polycarbonate resin. The preparation methods and characteristics of these special polycarbonate resins are described in detail in Japanese Unexamined Patent Publication No. 6-172508, Japanese Unexamined Patent Publication No. 8-27370, Japanese Unexamined Patent Publication No. 2001-55435 and Japanese Unexamined Patent Publication No. 2002-117580.

[0034] It should be noted that among the various polycarbonate resins mentioned above, the polycarbonate resin whose water absorption rate and Tg (glass transition temperature) are within the following ranges by adjusting the copolymer composition etc. is particularly preferred in fields requiring morphological stability because the polymer itself has good hydrolysis resistance and is also particularly excellent in low warpage after molding.

[0035] (i) a polycarbonate resin having a water absorption of 0.05 to 0.15%, preferably 0.06 to 0.13% and a Tg of 120 to 180°C, or (ii) a polycarbonate resin having a Tg of 160 to 250°C, preferably 170 to 230°C, and a water absorption of 0.10 to 0.30%, preferably 0.13 to 0.30%, more preferably 0.14 to 0.27%.

[0036] Here, the water absorption of the polycarbonate resin is a value obtained by measuring the water content of a disk-shaped test piece having a diameter of 45 mm and a thickness of 3.0 mm after immersion in water at 23° C. for 24 hours in accordance with ISO 62-1980. In addition, Tg (glass transition temperature) is a value obtained by differential scanning calorimetry (DSC) in accordance with JIS K7121.

[0037] As the carbonate precursor, carbonyl halide, carbonic acid diester, or halogenated formates can be used. Specific examples thereof include phosgene, diphenyl carbonate, and dihalogenated formates of dihydric phenols.

[0038] When utilizing interfacial polymerization to manufacture polycarbonate resin by above-mentioned dihydric phenol and carbonate precursor, can use catalyzer, terminal terminator, the antioxidant that is used to prevent dihydric phenol oxidation etc. as required.In addition, polycarbonate resin of the present invention comprises the branched polycarbonate resin that makes the copolymerization of the polyfunctional aromatic compound above trifunctional, the polyester carbonate resin that makes the copolymerization of the difunctional carboxylic acid of aromatic or aliphatic (comprising alicyclic), the copolymerization polycarbonate resin that makes the copolymerization of difunctional alcohol (comprising alicyclic) and the polyester carbonate resin that makes the copolymerization of above-mentioned difunctional carboxylic acid and difunctional alcohol together.In addition, can be the mixture that 2 or more of the polycarbonate resin that obtain are mixed.

[0039] The branched polycarbonate resin can impart anti-drip properties to the thermoplastic resin composition of the present invention. Examples of the trifunctional or higher polyfunctional aromatic compound used in the branched polycarbonate resin include phloroglucinol, phloroglucinol, or 4,6-dimethyl-2,4,6-tris(4-hydroxydiphenyl)-2-heptene, 2,4,6-trimethyl-2,4,6-tris(4-hydroxyphenyl)heptane, 1,3,5-tris(4-hydroxyphenyl)benzene, 1,1,1-tris(4-hydroxyphenyl)ethane, 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane, 2,6-bis(2-hydroxy-5-methylbenzyl)-4-methyl Phenol, triphenols such as 4-{4-[1,1-bis(4-hydroxyphenyl)ethyl]benzene}-α,α-dimethylbenzylphenol, tetrakis(4-hydroxyphenyl)methane, bis(2,4-dihydroxyphenyl)ketone, 1,4-bis(4,4-dihydroxytriphenylmethyl)benzene, or trimellitic acid, pyromellitic acid, benzophenonetetracarboxylic acid and acid chlorides thereof, among which 1,1,1-tris(4-hydroxyphenyl)ethane and 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane are preferred, and 1,1,1-tris(4-hydroxyphenyl)ethane is particularly preferred.

[0040] The amount of the constituent units derived from the polyfunctional aromatic compound in the branched polycarbonate resin is preferably 0.01 to 1 mol%, more preferably 0.05 to 0.9 mol%, and further preferably 0.05 to 0.8 mol%, based on the total 100 mol% of the constituent units derived from the dihydric phenol and the constituent units derived from the polyfunctional aromatic compound. In addition, in particular, in the case of the melt transesterification method, branched structural units may be generated as a side reaction. The amount of the branched structural units is preferably 0.001 to 1 mol%, more preferably 0.005 to 0.9 mol%, and further preferably 0.01 to 0.8 mol%, based on the total 100 mol% of the constituent units derived from the dihydric phenol. It should be noted that the ratio of the branched structure can be adjusted by 1 It was calculated by H-NMR measurement.

[0041] The aliphatic difunctional carboxylic acid is preferably an α,ω-dicarboxylic acid. As the aliphatic difunctional carboxylic acid, for example, a linear saturated aliphatic dicarboxylic acid such as sebacic acid (decane dioic acid), dodecanedioic acid, tetradecanedioic acid, octadecanedioic acid, eicosanedioic acid, and an alicyclic dicarboxylic acid such as cyclohexanedicarboxylic acid can be preferably mentioned. As the difunctional alcohol, an alicyclic diol is more preferably used, for example, cyclohexanedimethanol, cyclohexanediol, and tricyclodecane dimethanol can be exemplified.

[0042] Reaction forms such as the interfacial polymerization method, the melt transesterification method, the carbonate prepolymer solid phase transesterification method, and the ring-opening polymerization method of a cyclic carbonate compound as the production method of the polycarbonate resin of the present invention are methods well known in various documents and patent publications.

[0043] When manufacturing the thermoplastic resin composition of the present invention, the viscosity average molecular weight of the polycarbonate resin is preferably 12500 to 32000, more preferably 16000 to 28000, and further preferably 18000 to 26000. Polycarbonate resins having a viscosity average molecular weight of less than 12500 may not provide good mechanical properties. On the other hand, resin compositions obtained from polycarbonate resins having a viscosity average molecular weight of more than 32000 may have poor molding processability.

[0044] The viscosity average molecular weight in the present invention is obtained as follows: First, using an Ostwald viscometer, a solution obtained by dissolving 0.7 g of polycarbonate in 100 ml of dichloromethane at 20° C. is used to obtain a specific viscosity (ηSP) calculated by the following formula:

[0045] Specific viscosity (ηSP) = (t-t0) / t0

[0046] [t0 is the dripping seconds of dichloromethane, t is the dripping seconds of the sample solution]

[0047] The viscosity average molecular weight M was calculated from the determined specific viscosity (ηSP) by the following mathematical formula.

[0048] ηSP / c=[η]+0.45×[η] 2 c (where [η] is the intrinsic viscosity)

[0049] [η] = 1.23 × 10 -4 M 0.83

[0050] c=0.7

[0051] It should be noted that the viscosity average molecular weight of the polycarbonate resin in the thermoplastic resin composition of the present invention is calculated by the following method. That is, the composition is mixed with 20 to 30 times its weight of dichloromethane to dissolve the soluble components in the composition. The above-mentioned soluble components are collected by diatomaceous earth filtration. The solvent in the obtained solution is then removed. The solid after the solvent is removed is fully dried to obtain a solid of the component dissolved in dichloromethane. The specific viscosity at 20°C is calculated in the same way as above from the solution obtained by dissolving 0.7 g of the above-mentioned solid in 100 ml of dichloromethane, and the viscosity average molecular weight M is calculated in the same way as above from the specific viscosity.

[0052] As the polycarbonate resin of the present invention, a polycarbonate-polydiorganosiloxane copolymer resin may also be used. The polycarbonate-polydiorganosiloxane copolymer resin is preferably a copolymer resin prepared by copolymerizing a dihydric phenol represented by the following general formula (1) and a hydroxyaryl-terminated polydiorganosiloxane represented by the following general formula (3).

[0053]

[0054] [In the above general formula (1), R 1 and R 2 Each independently represents a group selected from a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkyloxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 14 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group and a carboxyl group; when there are plural of each, they may be the same or different, e and f are each an integer of 1 to 4, and W is a single bond or at least one group selected from the groups represented by the following general formula (2).]

[0055]

[0056] [In the above general formula (2), R 11 , R 12 , R 13 , R 14 , R 15 , R16 , R 17 and R 18 Each independently represents a group selected from a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an aryl group having 6 to 14 carbon atoms, and an aralkyl group having 7 to 20 carbon atoms, and R 19 and R 20 Each independently represents a group selected from a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkyloxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 10 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxyl group. When there are a plurality of such groups, they may be the same or different. g is an integer of 1 to 10, and h is an integer of 4 to 7.]

[0057]

[0058] [In the above general formula (3), R 3 , R 4 , R 5 , R 6 , R 7 and R 8 are each independently a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms, R 9 and R 10 Each is independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms, p is a natural number, q is 0 or a natural number, and p+q is a natural number from 10 to 300. X is a divalent aliphatic group having 2 to 8 carbon atoms.]

[0059] Examples of the dihydric phenol (I) represented by the general formula (1) include 4,4'-dihydroxybiphenyl, bis(4-hydroxyphenyl)methane, 1,1-bis(4-hydroxyphenyl)ethane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 2,2-bis(4-hydroxy-3,3'-biphenyl)propane, 2,2-bis(4-hydroxy-3-isopropylphenyl)propane, 2 , 2-bis(3-tert-butyl-4-hydroxyphenyl)propane, 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)octane, 2,2-bis(3-bromo-4-hydroxyphenyl)propane, 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, 2,2-bis(3-cyclohexyl-4-hydroxyphenyl)propane, 1,1-bis(3-cyclohexyl-4-hydroxyphenyl)cyclohexane, bis(4-hydroxyphenyl)diphenylmethane, 9,9-bis(4-hydroxyphenyl)fluorene, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 1, 1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)cyclopentane, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxy-3,3'-dimethyl diphenyl ether, 4,4'-sulfonyl diphenol, 4,4'-dihydroxydiphenyl sulfoxide, 4,4'-dihydroxydiphenyl sulfide, 2,2'-dimethyl-4,4'-sulfonyl diphenol, 4,4'-dihydroxy-3,3'-dimethyl diphenyl sulfoxide, 4,4'-dihydroxy-3,3'-dimethyl diphenyl sulfide, 2,2'-diphenyl-4,4'-sulfonyl diphenol, 4,4 '-Dihydroxy-3,3'-diphenyldiphenyl sulfoxide, 4,4'-dihydroxy-3,3'-diphenyldiphenyl sulfide, 1,3-bis{2-(4-hydroxyphenyl)propyl}benzene, 1,4-bis{2-(4-hydroxyphenyl)propyl}benzene, 1,4-bis(4-hydroxyphenyl)cyclohexane, 1,3-bis(4-hydroxyphenyl)cyclohexane, 4,8-bis(4-hydroxyphenyl)tricyclo[5.2.1.02,6]decane, 4,4'-(1,3-adamantanediyl)diphenol, 1,3-bis(4-hydroxyphenyl)-5,7-dimethyladamantane, etc.

[0060] Among them, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 4,4'-sulfonyldiphenol, 2,2'-dimethyl-4,4'-sulfonyldiphenol, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 1,3-bis{2-(4-hydroxyphenyl)propyl}benzene, and 1,4-bis{2-(4-hydroxyphenyl)propyl}benzene are preferred, and 2,2-bis(4-hydroxyphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane (BPZ), 4,4'-sulfonyldiphenol, and 9,9-bis(4-hydroxy-3-methylphenyl)fluorene are particularly preferred. Among them, 2,2-bis(4-hydroxyphenyl)propane is most preferred because of its excellent strength and good durability. In addition, these may be used alone or in combination of two or more.

[0061] As the hydroxyaryl-terminated polydiorganosiloxane represented by the general formula (3), for example, the following compounds are preferably used.

[0062]

[0063] Hydroxyaryl-terminated polydiorganosiloxane (II) is easily manufactured by hydrosilylation of phenols having olefinic unsaturated carbon-carbon bonds, preferably vinylphenol, 2-allylphenol, isopropenylphenol, 2-methoxy-4-allylphenol, at the end of a polysiloxane chain having a specified degree of polymerization. Among them, (2-allylphenol)-terminated polydiorganosiloxane and (2-methoxy-4-allylphenol)-terminated polydiorganosiloxane are preferred, and (2-allylphenol)-terminated polydimethylsiloxane and (2-methoxy-4-allylphenol)-terminated polydimethylsiloxane are particularly preferred. Hydroxyaryl-terminated polydiorganosiloxane (II) preferably has a molecular weight distribution (Mw / Mn) of 3 or less. In order to exhibit better low outgassing properties and low temperature impact properties during high temperature molding, the above molecular weight distribution (Mw / Mn) is more preferably 2.5 or less, and further preferably 2 or less. If the upper limit of the above preferred range is exceeded, the amount of outgassing generated during high temperature molding may be large and the low temperature impact resistance may be poor.

[0064] In order to achieve high impact resistance, the diorganosiloxane polymerization degree (p+q) of the hydroxyaryl-terminated polydiorganosiloxane (II) is preferably 10 to 300. The diorganosiloxane polymerization degree (p+q) is preferably 10 to 200, more preferably 12 to 150, and further preferably 14 to 100. If the degree of polymerization is below the lower limit of the preferred range, the impact resistance that is a characteristic of the polycarbonate-polydiorganosiloxane copolymer cannot be effectively exhibited, while if the degree of polymerization exceeds the upper limit of the preferred range, the appearance is poor.

[0065] The content of polydiorganosiloxane in the total weight of the polycarbonate-polydiorganosiloxane copolymer resin used in component A-1 is preferably 0.1 to 50% by weight. The content of the polydiorganosiloxane component is more preferably 0.5 to 30% by weight, and further preferably 1 to 20% by weight. When it is above the lower limit of the preferred range, the impact resistance and flame retardancy are excellent, and when it is below the upper limit of the preferred range, it is not easily affected by the molding conditions and it is easy to obtain a stable appearance. The degree of polymerization of the polydiorganosiloxane and the content of the polydiorganosiloxane can be adjusted by 1 Calculated by H-NMR measurement.

[0066] In the present invention, the hydroxyaryl-terminated polydiorganosiloxane (II) may be used alone or in combination of two or more.

[0067] Furthermore, other comonomers other than the dihydric phenol (I) and the hydroxyaryl-terminated polydiorganosiloxane (II) may be used in an amount of 10% by weight or less based on the total weight of the copolymer without hindering the present invention.

[0068] In the present invention, a mixed solution containing an oligomer having a terminal chloroformate group is prepared in advance by reacting a dihydric phenol (I) with a carbonate-forming compound in a mixed solution of a water-insoluble organic solvent and an aqueous alkali solution.

[0069] When generating oligomers of dihydric phenol (I), the total amount of dihydric phenol (I) used in the method of the present invention can be used to form oligomers at one time, or a part of it can be added as a post-added monomer as a reaction raw material in the interfacial polycondensation reaction of the latter stage. The post-added monomer refers to a monomer added in order to quickly carry out the polycondensation reaction of the latter stage, and it is not necessary to add it deliberately when it is not necessary.

[0070] The method of the oligomer production reaction is not particularly limited, but is usually preferably a method in which the reaction is carried out in a solvent in the presence of an acid binder.

[0071] The ratio of the carbonate-forming compound to be used may be appropriately adjusted in consideration of the stoichiometric ratio (equivalent) of the reaction. In addition, when a gaseous carbonate-forming compound such as phosgene is used, it is preferably blown into the reaction system.

[0072] As above-mentioned acid binding agent, for example, organic bases such as alkali metal hydroxides such as sodium hydroxide, potassium hydroxide, alkali metal carbonates such as sodium carbonate, potassium carbonate, pyridine or their mixture etc. can be used. The usage ratio of acid binding agent is also as above-mentioned just as long as the stoichiometric ratio (equivalent) of reaction is considered and suitably determined. Specifically, preferably use the acid binding agent that is 2 equivalents or slightly excessive compared with 2 equivalents with respect to the mole number (usually 1 mole is equivalent to 2 equivalents) of the dihydric phenol (I) that is used to form oligomer.

[0073] As the above-mentioned solvent, a solvent inactive to various reactions, such as a solvent used in the manufacture of known polycarbonates, can be used alone or as a mixed solvent. Representative examples include hydrocarbon solvents such as xylene, and halogenated hydrocarbon solvents represented by methylene chloride and chlorobenzene. It is particularly preferred to use halogenated hydrocarbon solvents such as methylene chloride.

[0074] The reaction pressure for generating oligomers is not particularly limited and may be any one of normal pressure, pressurization, and reduced pressure. It is usually advantageous to conduct the reaction under normal pressure. The reaction temperature is selected from the range of -20 to 50°C. In most cases, water cooling or ice cooling is preferred because of the heat generated by polymerization. The reaction time is affected by other conditions and cannot be generalized. It is usually carried out within 0.2 to 10 hours. The pH range of the oligomer generation reaction is the same as the known interfacial reaction conditions, and the pH is usually adjusted to 10 or more.

[0075] In the present invention, after a mixed solution containing oligomers of a dihydric phenol (I) having terminal chloroformate groups is obtained, a hydroxyaryl-terminated polydiorganosiloxane (II) represented by the general formula (3) which has been highly purified to have a molecular weight distribution (Mw / Mn) of 3 or less is added to the dihydric phenol (I) while stirring the mixed solution, and the hydroxyaryl-terminated polydiorganosiloxane (II) and the oligomer are subjected to interfacial polycondensation to obtain a polycarbonate-polydiorganosiloxane copolymer.

[0076]

[0077] (In the above general formula (3), R 3 , R 4 , R 5 , R 6 , R 7 and R 8 are each independently a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms, R 9 and R 10Each is independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms, p is a natural number, q is 0 or a natural number, and p+q is a natural number from 10 to 300. X is a divalent aliphatic group having 2 to 8 carbon atoms.

[0078] When carrying out interfacial polycondensation reaction, it is possible to consider that the stoichiometric ratio (equivalent) of the reaction is appropriately added with an acid binding agent. As an acid binding agent, for example, organic bases such as alkali metal hydroxides such as sodium hydroxide, potassium hydroxide, alkali metal carbonates such as sodium carbonate, potassium carbonate, pyridine, or mixtures thereof, etc. can be used. Specifically, when a part of the hydroxyaryl-terminated polydiorganosiloxane (II) or the dihydric phenol (I) as described above is added as a post-addition monomer in the reaction stage, it is preferred to use a base that is 2 equivalents or more than 2 equivalents relative to the total mole number (usually 1 mole is equivalent to 2 equivalents) of the dihydric phenol (I) and the hydroxyaryl-terminated polydiorganosiloxane (II) of the post-addition part.

[0079] The polycondensation of the oligomer of the dihydric phenol (I) and the hydroxyaryl-terminated polydiorganosiloxane (II) by an interfacial polycondensation reaction is carried out by vigorously stirring the mixed liquid.

[0080] In the above-mentioned polymerization reaction, a terminal terminator or a molecular weight regulator is usually used. As the terminal terminator, compounds having a monophenolic hydroxyl group can be cited, and in addition to common phenol, p-tert-butylphenol, p-cumylphenol, tribromophenol, etc., long-chain alkylphenols, aliphatic acid chlorides, aliphatic carboxylic acids, hydroxybenzoic acid alkyl esters, hydroxyphenyl alkyl esters, alkyl ether phenols, etc. can also be exemplified. The amount used is 100 to 0.5 moles, preferably 50 to 2 moles, relative to 100 moles of all diphenol compounds used. Of course, two or more compounds can also be used in combination.

[0081] In order to promote the polycondensation reaction, a catalyst such as a tertiary amine such as triethylamine or a quaternary ammonium salt may be added.

[0082] The reaction time of the above polymerization reaction is preferably 30 minutes or longer, more preferably 50 minutes or longer. If necessary, a small amount of an antioxidant such as sodium sulfite or hydrogen sulfide may be added.

[0083] A branching agent can be used together with the above-mentioned dihydric phenolic compound to prepare a branched polycarbonate-polydiorganosiloxane. Examples of the trifunctional or higher polyfunctional aromatic compound used in the branched polycarbonate-polydiorganosiloxane copolymer resin include phloroglucinol, phloroglucinol, or 4,6-dimethyl-2,4,6-tris(4-hydroxydiphenyl)-2-heptene, 2,4,6-trimethyl-2,4,6-tris(4-hydroxyphenyl)heptane, 1,3,5-tris(4-hydroxyphenyl)benzene, 1,1,1-tris(4-hydroxyphenyl)ethane, 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane, 2,6-bis(2-hydroxy-5-methylbenzyl)ethane, -4-methylphenol, 4-{4-[1,1-bis(4-hydroxyphenyl)ethyl]benzene}-α,α-dimethylbenzylphenol and other triphenols, tetrakis(4-hydroxyphenyl)methane, bis(2,4-dihydroxyphenyl)ketone, 1,4-bis(4,4-dihydroxytriphenylmethyl)benzene, or trimellitic acid, pyromellitic acid, benzophenonetetracarboxylic acid and their acid chlorides, among which 1,1,1-tris(4-hydroxyphenyl)ethane and 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane are preferred, and 1,1,1-tris(4-hydroxyphenyl)ethane is particularly preferred. The ratio of the multifunctional compound in the branched polycarbonate-polydiorganosiloxane copolymer resin is preferably 0.001 to 1 mol%, more preferably 0.005 to 0.9 mol%, further preferably 0.01 to 0.8 mol%, and particularly preferably 0.05 to 0.4 mol% in the total amount of the polycarbonate-polydiorganosiloxane copolymer resin. 1 Calculated by H-NMR measurement.

[0084] The reaction pressure can be any of reduced pressure, normal pressure, and pressurized pressure, and can usually be appropriately carried out under normal pressure or the self-pressure of the reaction system. The reaction temperature is selected from the range of -20 to 50°C. In most cases, water cooling or ice cooling is preferred because of the heat generated by polymerization. The reaction time varies depending on other conditions such as the reaction temperature, so it cannot be generally specified, and is usually carried out within 0.5 to 10 hours.

[0085] Depending on circumstances, the obtained polycarbonate-polydiorganosiloxane copolymer resin may be appropriately subjected to physical treatment (mixing, classification, etc.) and / or chemical treatment (polymerization reaction, crosslinking treatment, partial decomposition treatment, etc.) to obtain a polycarbonate-polydiorganosiloxane copolymer resin having a desired reduced viscosity [ηSP / c].

[0086] The obtained reaction product (crude product) can be subjected to various post-treatments such as known separation and purification methods to be recovered as a polycarbonate-polydiorganosiloxane copolymer resin having a desired purity (degree of purification).

[0087] The average size of the polydiorganosiloxane domain in the polycarbonate-polydiorganosiloxane copolymer resin molded product is preferably in the range of 1 to 40 nm. The average size is more preferably 1 to 30 nm, and further preferably 5 to 25 nm. When it is below the lower limit of the preferred range, the impact resistance and flame retardancy may not be fully exerted, and when it exceeds the upper limit of the preferred range, the impact resistance may not be stably exerted.

[0088] The average domain size and normalized variance of the polydiorganosiloxane domain of the polycarbonate-polydiorganosiloxane copolymer resin molded product of the present invention are evaluated by small angle X-ray scattering (SAXS). Small angle X-ray scattering refers to a method of measuring diffuse scattering and diffraction generated in a small angle region within a scattering angle (2θ) of less than 10°. In the small angle X-ray scattering method, if there is a region with different electron density of about 1 to 100 nm in a material, the diffuse scattering of X-rays is measured using the electron density difference. The particle size of the measured object is calculated based on the scattering angle and the scattering intensity. In the case of a polycarbonate-polydiorganosiloxane copolymer resin having an aggregate structure in which polydiorganosiloxane domains are dispersed in a matrix of a polycarbonate polymer, diffuse scattering of X-rays is generated using the electron density difference between the polycarbonate matrix and the polydiorganosiloxane domains. The scattering intensity I at each scattering angle (2θ) in the range of scattering angle (2θ) less than 10° is measured, and the small-angle X-ray scattering distribution is measured. It is assumed that the polydiorganosiloxane domain is a spherical domain, and there is no particle size distribution. Using commercially available analytical software, simulation is performed by the assumed particle size and the assumed particle size distribution model to obtain the average size and particle size distribution (normalized variance) of the polydiorganosiloxane domain. The small-angle X-ray scattering method can be used to accurately, simply and reproducibly measure the average size and particle size distribution of the polydiorganosiloxane domain dispersed in the matrix of the polycarbonate polymer that cannot be correctly measured by observation under a transmission electron microscope. The average domain size refers to the number average of the sizes of each domain. The normalized variance refers to a parameter obtained by normalizing the breadth of the particle size distribution with the average size. Specifically, it is a value obtained by normalizing the variance of the polydiorganosiloxane domain size with the average domain size, and is represented by the following formula (1).

[0089] Normalized variance (%) = δ / D av …(1)

[0090] In the above formula (1), δ is the standard deviation of the polydiorganosiloxane domain size, and Dav is the average domain size.

[0091] The terms "average domain size" and "normalized variance" used in the present invention represent the values ​​measured by the above-mentioned small-angle X-ray scattering method at a 1.0 mm thick portion of a three-stage plate produced by the method described in the examples. In addition, the analysis was performed using an isolated particle model that does not consider the interaction between particles (inter-particle interference).

[0092] <Component A-2: ABS resin>

[0093] The ABS resin used as the A-2 component of the present invention is a copolymer obtained by grafting polybutadiene with acrylonitrile and styrene. As styrene, styrene and α-methylstyrene are particularly preferably used. The proportion of the component grafted with the polybutadiene is preferably 95 to 20% by weight in 100% by weight of the ABS resin component, and particularly preferably 90 to 50% by weight. Moreover, relative to the total amount of acrylonitrile and styrene of 100% by weight, it is preferred that acrylonitrile is 5 to 50% by weight and styrene is 95 to 50% by weight. In addition, part of the component grafted with the above-mentioned polybutadiene can also be mixed with (meth) methyl acrylate, ethyl acrylate, maleic anhydride, N-substituted maleimide, etc., and their content ratio in the ABS resin component is preferably 15% by weight or less. In addition, the initiator, chain transfer agent, emulsifier, etc. used in the reaction can use various substances that have been known as needed. In the ABS resin of the present invention, the particle size of the polybutadiene is preferably 0.1 to 5.0 μm, more preferably 0.2 to 3.0 μm, and particularly preferably 0.3 to 1.5 μm. The particle size distribution of the polybutadiene may be either a single distribution or a distribution having two or more peaks, and in its form, the particles may form a single phase or may have a salami structure by containing an inclusion phase (オクルード phase) around the particles. In addition, it has been known that ABS resin contains a copolymer composed of acrylonitrile and styrene that are not grafted with a diene rubber component, and the ABS resin of the present invention may also contain a free polymer component generated during the above polymerization. The reduced viscosity (30°C) of the copolymer composed of the free acrylonitrile and styrene is preferably 0.2 to 1.0 dl / g, and more preferably 0.3 to 0.7 dl / g. In addition, the ratio of grafted acrylonitrile and styrene to polybutadiene is preferably 20 to 200% in terms of grafting rate (weight %), and more preferably 20 to 70%. The ABS resin can be produced by any method of bulk polymerization, suspension polymerization, and emulsion polymerization, but is particularly preferably produced by bulk polymerization. In the case of bulk polymerization, since the alkali metal salts from the emulsifier are not substantially contained, the thermal stability of the resin composition can be better ensured. In addition, the copolymerization method can be a single-stage copolymerization or a multi-stage copolymerization. In addition, it is also preferred to use a material obtained by blending a vinyl compound polymer obtained by copolymerizing acrylonitrile and styrene in the ABS resin obtained by the manufacturing method.

[0094] <Component A-3: polyester resin>

[0095] The polyester resin used as the component A-3 of the present invention is preferably a polyester resin in which 70 mol% or more of 100 mol% of the dicarboxylic acid components in the dicarboxylic acid components and the diol components forming the polyester are aromatic dicarboxylic acids, more preferably 90 mol% or more, most preferably 99 mol% or more.

[0096] Examples of the dicarboxylic acid include terephthalic acid, isophthalic acid, 2-chloroterephthalic acid, 2,5-dichloroterephthalic acid, 2-methylterephthalic acid, 4,4-stilbene dicarboxylic acid, 4,4-biphenyl dicarboxylic acid, phthalic acid, 2,6-naphthalene dicarboxylic acid, 2,7-naphthalene dicarboxylic acid, dibenzoic acid, bis(p-carboxyphenyl)methane, anthracene dicarboxylic acid, 4,4-diphenyl ether dicarboxylic acid, 4,4-diphenoxyethane dicarboxylic acid, 5-sodium sulfoisophthalate, and ethylene diphenyl terephthalic acid. These dicarboxylic acids may be used alone or in combination of two or more. In the polyester resin of the present invention, in addition to the above-mentioned aromatic dicarboxylic acid, less than 30 mol% of an aliphatic dicarboxylic acid component may be copolymerized. Specific examples thereof include adipic acid, sebacic acid, azelaic acid, dodecanedioic acid, 1,3-cyclohexanedicarboxylic acid, and 1,4-cyclohexanedicarboxylic acid.

[0097] As the diol component of the present invention, for example, ethylene glycol, diethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 2,2-dimethyl-1,3-propylene glycol, trans- or cis-2,2,4,4-tetramethyl-1,3-cyclobutanediol, 1,4-butanediol, neopentyl glycol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, decanediol, cyclohexanediol, p-xylene glycol, bisphenol A, tetrabromobisphenol A, tetrabromobisphenol A-bis(2-hydroxyethyl ether), etc. can be mentioned. They can be used alone or in combination of two or more. It should be noted that the dihydric phenol in the diol component is preferably 30 mol% or less.

[0098] Specific examples of polyester resins include polyethylene terephthalate (PET), polytrimethylene terephthalate, polybutylene terephthalate (PBT), polyethylene terephthalate, polyethylene naphthalate (PEN), polybutylene naphthalate (PBN), polyethylene-1,2-bis(phenoxy)ethane-4,4′-dicarboxylate, and copolymeric polyester resins such as polyethylene isophthalate / polyethylene terephthalate copolymers and polybutylene terephthalate / polybutylene isophthalate copolymers.

[0099] In addition, the terminal group structure of the polyester resin used in the present invention is not particularly limited, and the ratio of the hydroxyl group to the carboxyl group in the terminal group is almost equal, or the ratio of one side is larger. In addition, these terminal groups can be capped by reacting a compound reactive with the terminal group.

[0100] The method for producing the polyester resin used in the present invention can be carried out by conventional methods, in the presence of a polycondensation catalyst containing titanium, germanium, antimony, etc., while heating the dicarboxylic acid component and the above-mentioned diol component, and discharging the by-produced water or lower alcohol to the outside of the system. For example, as a germanium-based polymerization catalyst, examples include oxides, hydroxides, halides, alcohol salts, phenolates, etc. of germanium, and more specifically, examples include germanium oxide, germanium hydroxide, germanium tetrachloride, tetramethoxygermanium, etc. In addition, in the present invention, compounds such as manganese, zinc, calcium, and magnesium used in the ester exchange reaction that has always been known as the pre-stage of polycondensation can be used together, and after the ester exchange reaction is completed, the above-mentioned catalyst can be deactivated by using compounds such as phosphoric acid or phosphorous acid to carry out polycondensation. In addition, the method for producing the polyester resin can adopt any method of batch type or continuous polymerization type.

[0101] Among the above polyester resins, polyethylene terephthalate is particularly preferred. The polyethylene terephthalate of the present invention refers to a polymer obtained by polycondensation of terephthalic acid or its derivatives and 1,4-ethylene glycol or its derivatives, and includes a product obtained by copolymerization of other dicarboxylic acid components and other alkylene glycol components as described above.

[0102] The terminal group structure of polyethylene terephthalate is the same as described above, and is not particularly limited. It is more preferred that the terminal carboxyl group is less than the terminal hydroxyl group. In addition, the manufacturing method can also adopt the various methods described above, but the continuous polymerization method is preferred. This is because its quality stability is high and it is also cost-effective. In addition, as a polymerization catalyst, an organic titanium compound is preferably used. This is because the organic titanium compound has a tendency to have little effect on transesterification reactions, etc. As the organic titanium compound, as preferred specific examples, titanium tetrabutoxide, titanium isopropoxide, titanium oxalate, titanium acetate, titanium benzoate, titanium trimellitic acid, the reaction product of tetrabutyl titanate and trimellitic anhydride, etc. can be cited. The amount of the organic titanium compound used is preferably such that the titanium atom is in a ratio of 3 to 12 mg atomic % relative to the acid component constituting polyethylene terephthalate.

[0103] The molecular weight of the polyester resin of the present invention is not particularly limited, but the intrinsic viscosity measured at 35° C. using o-chlorophenol as a solvent is preferably 0.5 to 1.5, particularly preferably 0.6 to 1.2.

[0104] <Component A-4: AS resin>

[0105] The AS resin used as the A-4 component of the present invention is a copolymer of acrylonitrile and styrene. The AS resin has high stereoregularity such as syndiotactic polystyrene by using a catalyst such as a metallocene catalyst during its production. In addition, polymers and copolymers with narrow molecular weight distribution, block copolymers, and polymers and copolymers with high stereoregularity obtained by methods such as anionic living polymerization and free radical living polymerization can also be used according to circumstances.

[0106] <Component A-5: PS resin>

[0107] The PS resin used as the component A-5 in the present invention is a polymer of styrene.

[0108] <Component A-6: AAS resin>

[0109] The AAS resin used as the component A-6 of the present invention is a copolymer composed of acrylonitrile, styrene and an acrylic rubber component.

[0110] <Component B: Phosphonate>

[0111] The phosphonic acid ester used in the present invention can be a phosphonic acid monoester, a phosphonic acid diester, or a phosphonic acid triester, but a phosphonic acid triester is preferred. The number of carbon atoms of the ester can be various combinations of 1 to 22, but triethyl phosphonoacetate is most preferred. The acid value of the phosphonic acid ester is 0.01 to 0.30 mgKOH / g, preferably 0.01 to 0.20 mgKOH / g, and more preferably 0.05 to 0.15 mgKOH / g. Phosphonic acid esters having an acid value of less than 0.01 mgKOH / g are not practical in manufacturing, and when the acid value is greater than 0.30 mgKOH / g, discoloration and a decrease in strength during molding processing cannot be prevented. The determination of the acid value is carried out by titrating the alcohol solution of the phosphonic acid ester with a KOH alcohol solution using a potentiometric titration apparatus.

[0112] The content of component B is 0.001 to 1 part by weight, preferably 0.01 to 0.1 part by weight, and more preferably 0.01 to 0.07 part by weight relative to 100 parts by weight of component A. When the content of component B is less than 0.001 part by weight or exceeds 1 part by weight, discoloration during molding and a decrease in strength cannot be prevented.

[0113] <Component C: Inorganic filler>

[0114] The inorganic filler of component C can use conventionally known inorganic fillers, among which preferably at least one inorganic filler selected from the group consisting of (C-1) glass fiber (component C-1), (C-2) plate-shaped glass filler (component C-2), (C-3) fibrous carbon filler (component C-3), (C-4) non-fibrous carbon filler (component C-4) and (C-5) silicate mineral (component C-5).

[0115] The content of component C is preferably 1 to 150 parts by weight, more preferably 3 to 140 parts by weight, and further preferably 5 to 130 parts by weight relative to 100 parts by weight of component A. When the content of component C is less than 1 part by weight, sufficient rigidity may not be obtained, and when the content exceeds 150 parts by weight, the strength and flame retardancy during molding may decrease.

[0116] <Component C-1: Glass fiber>

[0117] The glass fiber used in the present invention is not particularly limited to the glass composition of A glass, C glass, E glass, etc., and may contain components such as TiO2, SO3, P2O5, etc. according to the circumstances. Among them, E glass (alkali-free glass) combined with thermoplastic resin is more preferred. And two or more of these glass fibers may also be used in combination. Glass fiber is made by quenching molten glass while stretching it by various methods to form a specified fiber or powder. The quenching and stretching conditions at this time are not particularly limited. In addition, the shape of the cross section can be an elliptical, cocoon-shaped, trilobal, or other shapes other than a perfect circle, in addition to a perfect circle. And circular glass fibers and glass fibers in shapes other than a perfect circle can be mixed. Among them, circular glass fibers are more preferred. In addition, from the perspective of obtaining better mechanical strength, it is preferred that these glass fibers be pre-treated with coupling agents such as isocyanate compounds, organic silane compounds, organic titanate compounds, organic borane compounds, and epoxy compounds before use. In the case of swellable layered silicates, organic The glass fiber used in the present invention preferably has a diameter (D) of 6 to 13 μm, a cut length (L) of 30 μm to 9 mm, and an L / D ratio of 2.3 to 1500.

[0118] <C-2: Plate glass filler>

[0119] Examples of the plate-shaped glass filler include glass flakes, metal-coated glass flakes, and metal oxide-coated glass flakes.

[0120] The glass flakes as the matrix of the plate-shaped glass filler are plate-shaped glass fillers manufactured by methods such as cylinder blowing and sol-gel methods. The size of the raw material of the above-mentioned glass flakes can also be selected from various sizes according to the degree of crushing and classification. The average particle size of the glass flakes used in the raw material is preferably 10 to 1000 μm, more preferably 20 to 500 μm, and further preferably 30 to 300 μm. This is because the average particle size in the above range is excellent in both operability and molding processability. Usually, the plate-shaped glass filler is broken due to the melt kneading process with the resin, and its average particle size becomes smaller. The number average particle size of the plate-shaped glass filler in the thermoplastic resin composition is preferably 10 to 200 μm, more preferably 15 to 100 μm, and further preferably 20 to 80 μm. It should be noted that the above-mentioned number average particle size is a value calculated by an image obtained by optical microscope observation of the residue of the plate-shaped glass filler taken during the high-temperature ashing of the molded product, the dissolution by solvent, and the decomposition by reagent, etc., and using an image analysis device. In addition, this value is obtained by a method in which the length below the sheet thickness is not counted when calculating the above value. In addition, the thickness is preferably 0.5 to 10 μm, more preferably 1 to 8 μm, and further preferably 1.5 to 6 μm. The plate-shaped glass filler having the above number average particle size and thickness sometimes achieves good mechanical strength, appearance, and molding processability.

[0121] The glass composition of the plate-shaped glass filling material can adopt various glass compositions represented by A glass, C glass and E glass, etc., without special limitation. The glass filling material can contain components such as TiO2, SO3 and P2O5 as needed. Among these, E glass (alkali-free glass) is more preferred. In addition, from the perspective of improving mechanical strength, it is preferred to use a known surface treatment agent, such as a silane coupling agent, a titanate coupling agent or an aluminate coupling agent, to perform surface treatment on the plate-shaped glass filling material. In addition, the plate-shaped glass filling material preferably uses a material that has been subjected to a bundling treatment using an olefin resin, a styrene resin, an acrylic resin, a polyester resin, an epoxy resin and a polyurethane resin. The amount of the bundling agent attached to the bundled plate-shaped glass filling material is preferably 0.5 to 8% by weight, and more preferably 1 to 4% by weight in 100% by weight of the plate-shaped glass filling material.

[0122] In addition, the plate-shaped glass filling material includes a filling material whose surface is coated with different kinds of materials. As the different kinds of materials, metals and metal oxides are preferably exemplified. As metals, silver, copper, nickel and aluminum can be exemplified. In addition, as metal oxides, titanium oxide, cerium oxide, zirconium oxide, iron oxide, aluminum oxide and silicon oxide can be exemplified. The method for coating the surface of the different kinds of materials is not particularly limited, and for example, various known plating methods (for example, electrolytic plating, electroless plating, hot dip plating, etc.), vacuum evaporation method, ion plating method, CVD method (for example, thermal CVD, MOCVD, plasma CVD, etc.), PVD method and sputtering method can be cited.

[0123] <Component C-3: Fibrous carbon filler>

[0124] As fibrous carbon filling materials, for example, carbon fiber, metal-coated carbon fiber, carbon milled fiber, vapor-grown carbon fiber and carbon nanotubes can be cited. The fiber diameter of the carbon nanotube is 0.003 to 0.1 μm, and it can be any one of a single layer, a double layer and a multilayer, preferably a multilayer (so-called MWCNT). Among these, carbon fiber and metal-coated carbon fiber are preferred from the aspects of excellent mechanical strength and the ability to impart good electrical conductivity. It should be noted that good electrical conductivity has become one of the important characteristics required of resin materials in digital precision equipment (such as digital cameras) in recent years.

[0125] As carbon fiber, cellulose, polyacrylonitrile and asphalt can be used. In addition, carbon fiber obtained by the following method can also be used: spinning or molding a raw material composition consisting of a polymer and a solvent formed by an aromatic sulfonic acid or its salt via a methylene-type bond, followed by a spinning method represented by a carbonization method without a non-melting process. In addition, general-purpose, medium elastic modulus and high elastic modulus types can all be used. Among these, the high elastic modulus type of the polyacrylonitrile system is particularly preferred. In addition, the average fiber diameter of the carbon fiber is not particularly limited, usually 3 to 15 μm, preferably 5 to 13 μm. Carbon fibers with an average fiber diameter in the above range can sometimes show good mechanical strength and fatigue properties without damaging the appearance of the molded product. In addition, the preferred fiber length of the carbon fiber is 60 to 500 μm, preferably 80 to 400 μm, and particularly preferably 100 to 300 μm, based on the number average fiber length in the thermoplastic resin composition. It should be noted that the above-mentioned number average fiber length is a value calculated by an image analyzer by observing the residue of carbon fibers taken from the high-temperature ashing of the molded product, dissolution by a solvent, and decomposition by a reagent, etc. using an optical microscope. In addition, this value is a value obtained by a method in which the length below the fiber length is not counted when calculating the above value. The aspect ratio of the carbon fiber is preferably in the range of 10 to 200, more preferably in the range of 15 to 100, and further preferably in the range of 20 to 50. The aspect ratio refers to the value obtained by dividing the average fiber length by the average fiber diameter.

[0126] In addition, the surface of the carbon fiber is preferably subjected to oxidation treatment for the purpose of improving adhesion with the matrix resin and improving mechanical strength. The oxidation treatment method is not particularly limited, and for example, preferred examples include: (1) a method of treating the fibrous carbon filler with an acid or an alkali or a salt thereof, or an oxidizing gas; (2) a method of calcining the fiber or fibrous carbon filler capable of being converted into a fibrous carbon filler at a temperature of 700° C. or higher in the presence of an inert gas containing an oxygen-containing compound; and (3) a method of heat-treating the fibrous carbon filler in the presence of an inert gas after the oxidation treatment.

[0127] Metal-coated carbon fiber is obtained by coating a metal layer on the surface of carbon fiber. As metal, silver, copper, nickel and aluminum can be mentioned, and nickel is preferred from the viewpoint of corrosion resistance of the metal layer. As a method of coating the metal, various methods previously described in the surface coating of plate-shaped glass fillers using different types of materials can be adopted. Among them, the plating method is preferably used. In addition, in the case of the above-mentioned metal-coated carbon fiber, as the base carbon fiber, the carbon fiber mentioned as the above-mentioned carbon fiber can also be used. The thickness of the metal coating layer is preferably 0.1 to 1 μm, and more preferably 0.15 to 0.5 μm. More preferably, it is 0.2 to 0.35 μm.

[0128] The carbon fibers and metal-coated carbon fibers are preferably subjected to a bundling treatment with olefin resins, styrene resins, acrylic resins, polyester resins, epoxy resins, polyurethane resins, etc. In particular, fibrous carbon fillers treated with polyurethane resins and epoxy resins are preferred in the present invention because of their excellent mechanical strength.

[0129] <Component C-4: Non-fibrous carbon filler>

[0130] As non-fibrous carbon filler materials, for example, carbon black, graphite, fullerene, etc. can be cited. Among these, carbon black and graphite are preferred from the aspects of mechanical strength, moisture and heat resistance, and thermal stability. As carbon black, from the aspect of conductivity, carbon black with a DBP oil absorption of 100ml / 100g to 500ml / 100g is preferred. The carbon black is generally acetylene black or Ketjen black. Specifically, for example, DENKA BLACK manufactured by Denki Kagaku Kogyo Co., Ltd., VULCAN XC-72 and BP-2000 manufactured by Cabot Corporation, Ketjen black EC and Ketjen black EC-600JD manufactured by LION Corporation, etc. can be cited.

[0131] As graphite, natural graphite or various artificial graphites whose mineral name is called graphite can be used. As natural graphite, earthy graphite, scaly graphite (also called Vein Graphite of blocky graphite) and scaly graphite (Flake Graphite) can be used. In addition, artificial graphite is formed by heat-treating amorphous carbon and artificially carrying out the orientation of irregularly arranged tiny graphite crystals, except artificial graphite generally used for carbon materials, also includes floating graphite (kishgraphite), decomposed graphite and pyrolytic graphite etc.. Generally used for artificial graphite used in carbon materials is usually manufactured by graphitization treatment with petroleum coke and coal-based pitch coke as main raw materials.

[0132] The graphite of the present invention may include expanded graphite that can be thermally expanded by a treatment represented by an acid treatment, or graphite that has been subjected to the expansion treatment. The particle size of the graphite is preferably in the range of 2 to 300 μm. The above-mentioned particle size is more preferably 5 to 200 μm, further preferably 7 to 100 μm, and particularly preferably 7 to 50 μm. By satisfying the above-mentioned range, good mechanical strength and appearance of the molded product can sometimes be achieved. On the other hand, if the average particle size is less than 2 μm, the effect of improving rigidity sometimes becomes smaller, and if the average particle size exceeds 300 μm, the impact resistance sometimes decreases significantly, and the so-called graphite floating on the surface of the molded product becomes obvious, so it is not preferred.

[0133] The fixed carbon content of the graphite of the present invention is preferably 80% by weight or more, more preferably 90% by weight or more, and further preferably 98% by weight or more. In addition, the volatile components of the graphite of the present invention are preferably 3% by weight or less, more preferably 1.5% by weight or less, and further preferably 1% by weight or less.

[0134] The average particle size of graphite in the present invention refers to the particle size of graphite itself before it becomes a resin composition, and the particle size refers to the particle size determined by a laser diffraction / scattering method.

[0135] Furthermore, the graphite surface may be subjected to surface treatment such as epoxy treatment, urethane treatment, silane coupling treatment, and oxidation treatment in order to increase affinity with the thermoplastic resin, as long as the properties of the composition of the present invention are not impaired.

[0136] <C-5 component: silicate mineral>

[0137] As the inorganic filler in the present invention, silicate minerals composed of at least a metal oxide component and a SiO2 component can be cited, preferably orthosilicates, disilicates, cyclic silicates and chain silicates, etc. The silicate mineral can be in a crystalline state, and the crystal can be any form that can be adopted by each silicate mineral. In addition, the shape of the crystal can also be various shapes such as fibrous and plate-like.

[0138] Silicate minerals may be any compound in a composite oxide, an oxyacid salt (composed of an ionic lattice), or a solid solution. The composite oxide may be any combination of two or more single oxides, or any combination of two or more single oxides and oxyacid salts. The solid solution may be any solid solution of two or more metal oxides, or any solid solution of two or more oxyacid salts. In addition, it may be a hydrate. The form of crystal water in the hydrate may be any of the following forms: a form in which Si-OH enters in the form of hydrogen silicate ions, a form in which hydroxide ions (OH - ) in the form of ionic entry into metal cations, and in the form of H2O molecules that enter the gaps in the structure.

[0139] As the silicate mineral, an artificially synthesized product corresponding to a natural product may be used. As the artificially synthesized product, a silicate mineral obtained by various conventionally known methods, such as various synthesis methods utilizing solid reaction, hydrothermal reaction, and ultrahigh pressure reaction, may be used.

[0140] Specific examples of silicate minerals in each metal oxide component include the following silicate minerals: Here, the expressions in parentheses are names of minerals containing the above-mentioned silicate minerals as main components, and indicate that the compounds in parentheses can be used as exemplified metal salts.

[0141] Examples of substances containing K2O in their components include K2O·SiO2, K2O·4SiO2·H2O, K2O·Al2O3·2SiO2 (hexagonal potassium pyroxene), K2O·Al2O3·4SiO2 (leucite), and K2O·Al2O3·6SiO2 (orthoclase).

[0142] Substances containing Na2O in their components include Na2O·SiO2 and its hydrates, Na2O·2SiO2, 2Na2O·SiO2, Na2O·4SiO2, Na2O·3SiO2·3H2O, Na2O·Al2O3·2SiO2, Na2O·Al2O3·4SiO2 (jadeite), 2Na2O·3CaO·5SiO2, 3Na2O·2CaO·5SiO2, and Na2O·Al2O3·6SiO2 (albite), etc.

[0143] Substances containing Li2O in their components include Li2O·SiO2, 2Li2O·SiO2, Li2O·SiO2·H2O, 3Li2O·2SiO2, Li2O·Al2O3·4SiO2 (petalite), Li2O·Al2O3·2SiO2 (eucryptite), and Li2O·Al2O3·4SiO2 (spodumene).

[0144] As the material containing BaO as a component, BaO.SiO2, 2BaO.SiO2, BaO.Al2O3.2SiO2 (barium feldspar), and BaO.TiO2.3SiO2 (benzimidite) etc. are mentioned.

[0145] As substances containing CaO in their components, there can be mentioned 3CaO·SiO2 (alite of cement clinker mineral), 2CaO·SiO2 (belite of cement clinker mineral), 2CaO·MgO·2SiO2 (magnesia chalcite), 2CaO·Al2O3·SiO2 (calcium feldspar), a solid solution of magnesia chalcite and calcium feldspar (calcium feldspar), CaO·SiO2 (wollastonite (including both α-type and β-type)), CaO·MgO·2SiO2 (diopside), CaO·MgO·SiO2 (diopside), 3CaO·MgO·2SiO2 (magnesia olivine), CaO·Al2O3·2SiO2 (calcium feldspar), 5CaO·6SiO2·5H2O (tobermorite, other tobermorite such as 5CaO·6SiO2·9H2O) and the like. hydrates, wollastonite group hydrates such as 2CaO·SiO2·H2O (wollastonite), wollastonite group hydrates such as 6CaO·6SiO2·H2O (xonotlite), wollastonite group hydrates such as 2CaO·SiO2·2H2O (white calcium zeolite), CaO·Al2O3·2SiO2·H2O (hard calcium zeolite), CaO·FeO·2SiO2 (ferrocalcium pyroxene), 3CaO·2SiO2 (wollastonite), 3CaO·Al2O3·3SiO2 (grossularite), 3CaO·Fe2O3·3SiO2 (andradite), 6CaO·4Al2O3·FeO·SiO2 (pleochroite), as well as clinzoisite, carnelian, allantois, fusiliers, axestone, scawtite and common pyroxene.

[0146] In addition, as a silicate mineral containing CaO as a component, Portland cement can be cited. The type of Portland cement is not particularly limited, and any of ordinary, early strength, super early strength, medium heat, sulfate-resistant, white, etc. can be used. In addition, various mixed cements such as blast furnace cement, silica cement, fly ash cement, etc. can also be used as component B. In addition, as other silicate minerals containing CaO as a component, blast furnace slag, ferrite, etc. can be cited.

[0147] As a substance containing ZnO in its composition, ZnO·SiO2, 2ZnO·SiO2 (sonite) and 4ZnO·2SiO2·H2O (hemimorphite) can be cited. As a substance containing MnO in its composition, MnO·SiO2, 2MnO·SiO2, CaO·4MnO·5SiO2 (rhodonite) and galaxyite can be cited. As a substance containing FeO in its composition, FeO·SiO2 (orthopyroxene), 2FeO·SiO2 (fayalite), 3FeO·Al2O3·3SiO2 (aluminum garnet) and 2CaO·5FeO·8SiO2·H2O (ferroactinolite) can be cited.

[0148] As the material containing CoO as its component, there are CoO·SiO2, 2CoO·SiO2, etc.

[0149] As the material containing MgO in its component, there are MgO·SiO2 (talc, enstatite), 2MgO·SiO2 (forsterite), 3MgO·Al2O3·3SiO2 (pyrope), 2MgO·2Al2O3·5SiO2 (cordierite), 2MgO·3SiO2·5H2O, 3MgO·4SiO2·H2O (talc), 5MgO·8SiO2·9H2O (attapulgite), 4MgO·6SiO2·7H2O (pyrope), 2MgO·3SiO2·5H2O, 3MgO·4SiO2·H2O (talc), 5MgO·8SiO2·9H2O (attapulgite), 4MgO·6SiO2·7H2O (hexadecene ...hexadecene), 5MgO·8SiO2·9H2O (hexadecene), 2MgO·3SiO2·5H2O, 3MgO·4SiO2·H2O (hexadecene), 5MgO·6SiO2·7H2O (hexadecene), 2MgO·3SiO2·5H2O, 3MgO·4SiO2·H2O (hexadecene), 5 2O (sepiolite), 3MgO·2SiO2·2H2O (chrysolite), 5MgO·2CaO·8SiO2·H2O (tremolite), 5MgO·Al2O3·3SiO2·4H2O (chlorite), K2O·6MgO·Al2O3·6SiO2·2H2O (phlogopite), Na2O·3MgO·3Al2O3·8SiO2·H2O (glaucophane), as well as magnesia tourmaline, anthophyllite, ferromagnesian amphibole, vermiculite, montmorillonite, etc.

[0150] Examples of substances containing Fe2O3 as components include Fe2O3·SiO2 and the like.

[0151] Examples of materials containing ZrO 2 as components include ZrO 2 ·SiO 2 (zircon) and AZS refractory.

[0152] Substances containing Al2O3 in their components include Al2O3·SiO2 (sillimanite, andalusite, kyanite), 2Al2O3·SiO2, Al2O3·3SiO2, 3Al2O3·2SiO2 (mullite), Al2O3·2SiO2·2H2O (kaolinite), Al2O3·4SiO2·H2O (phyllite), Al2O3·4SiO2·H2O (bentonite), K2O·3Na2O·4Al2O3·8SiO2 (nepheline), K2O·3Al2O3·6SiO2·2H2O (muscovite, sericite), K2O·6MgO·Al2O3·6SiO2·2H2O (phlogopite), various zeolites, fluorphlogopite and biotite, etc.

[0153] Among the above-mentioned silicate minerals, talc, mica, and wollastonite are particularly preferred because they have an excellent balance between rigidity and impact resistance, are excellent in moisture and heat resistance, thermal stability, and appearance, and are easily available.

[0154] <Component D: Flame retardant>

[0155] The flame retardant of component D may be any of various compounds known as flame retardants for polycarbonate resins, and preferably at least one flame retardant selected from the group consisting of (D-1) halogenated carbonate compounds (component D-1), (D-2) phosphate compounds (component D-2), (D-3) phosphazene compounds (component D-3), (D-4) sulfonic acid metal salts (component D-4), and (D-5) organosilicon compounds (component D-5).

[0156] The content of component D is preferably 0.01 to 25 parts by weight, more preferably 0.015 to 22 parts by weight, and further preferably 0.02 to 20 parts by weight relative to 100 parts by weight of component A. When the content of component D is 0.01 to 25 parts by weight, it is sometimes possible to obtain both a sufficient flame retardancy improvement effect and prevention of strength reduction during molding.

[0157] <Component D-1: Halogenated carbonate compound>

[0158] As the halogenated carbonate compound used in the present invention, it is preferred to use a halogenated carbonate compound having a structural unit represented by the following general formula (4) accounting for at least 60 mol % of all structural units and having a specific viscosity of 0.015 to 0.1.

[0159]

[0160] [In the general formula (4), X is a halogen atom, and R is an alkylene group having 1 to 4 carbon atoms, an alkylidene group having 1 to 4 carbon atoms, or -SO2-.]

[0161] In the above formula (4), R preferably represents a methylene group, an ethylene group, an isopropylene group, or -SO2-, and particularly preferably represents an isopropylene group. Also, X is preferably a bromine atom.

[0162] In the halogenated carbonate compound, the residual chloroformate terminal is few, and the terminal chlorine amount is preferably below 0.3ppm, more preferably below 0.2ppm. The terminal chlorine amount can be by dissolving the sample in methylene chloride, and adding 4-(p-nitrobenzyl) pyridine and terminal chlorine (terminal chloroformate) reaction, utilizing ultraviolet visible spectrophotometer (U-3200 made by Hitachi Manufacturing) to measure it and obtain. If the terminal chlorine amount is below 0.3ppm, the thermal stability of polycarbonate resin composition is better, and high temperature molding can be further carried out, and its result can provide the resin combination with more excellent molding processability.

[0163] In addition, the halogenated carbonate compound preferably has a small amount of residual hydroxyl terminals. More specifically, the amount of terminal hydroxyl groups is preferably 0.0005 mol or less, and more preferably 0.0003 mol or less, relative to 1 mol of the structural unit of the halogenated carbonate compound. The amount of terminal hydroxyl groups can be determined by dissolving the sample in deuterated chloroform and using 1The amount of terminal hydroxyl groups can be determined by measuring with the H-NMR method. If the amount of terminal hydroxyl groups is the above, the thermal stability of the polycarbonate resin composition may be further improved.

[0164] The specific viscosity of the halogenated carbonate compound is preferably in the range of 0.015 to 0.1, more preferably in the range of 0.015 to 0.08. The specific viscosity of the halogenated carbonate compound is calculated according to the formula used to calculate the viscosity average molecular weight of the polycarbonate resin as the component A-1 of the present invention.

[0165] The halogenated carbonate compounds are commercially available, and examples thereof include tetrabromobisphenol A carbonate oligomers (trade names FG-7000 and FG-8500) manufactured by Teijin Limited. These commercial products can be used in the present invention.

[0166] <Component D-2: Phosphate ester compound>

[0167] As the phosphate-based compound used in the present invention, a phosphate compound, particularly an aryl phosphate compound is preferred.

[0168] The molecular weight of the phosphate compound is preferably not less than 300. If the molecular weight is less than 300, the difference between the boiling point of the phosphate compound and the combustion temperature of the resin composition becomes large, and the phosphate compound may volatilize more during combustion, thereby reducing the effect as a flame retardant.

[0169] As the phosphate compound, various phosphate compounds known as flame retardants can be used, and more preferred are phosphate compounds represented by the following general formula (5) at least one.

[0170]

[0171] (In the general formula (5), X is a dihydric phenol residue derived from a dihydroxy compound selected from the group consisting of hydroquinone, resorcinol, bis(4-hydroxydiphenyl)methane, bisphenol A, dihydroxybiphenyl, dihydroxynaphthalene, bis(4-hydroxyphenyl)sulfone, bis(4-hydroxyphenyl)ketone and bis(4-hydroxyphenyl)sulfide, n is an integer of 0 to 5, or in the case of a mixture of phosphoric acid esters having different n numbers, is the average value thereof, and R 1 , R 2 , R 3 and R 4 Each is independently a monohydric phenol residue derived from an aromatic group selected from phenol, cresol, xylenol, isopropylphenol, butylphenol and p-cumylphenol.

[0172] The phosphate compound of the general formula may be a mixture of compounds having different n numbers. In the case of such a mixture, the average n number is preferably 0.5 to 1.5, more preferably 0.8 to 1.2, further preferably 0.95 to 1.15, and particularly preferably 1 to 1.14.

[0173] Preferred specific examples of the dihydric phenol from which X in the general formula (5) is derived include resorcinol, bisphenol A and dihydroxybiphenyl, among which resorcinol and bisphenol A are preferred.

[0174] As R in the above general formula (5) 1 , R 2 , R 3 and R 4 Preferred specific examples of the monohydric phenol include phenol, cresol, xylenol, and 2,6-dimethylphenol, among which phenol and 2,6-dimethylphenol are preferred.

[0175] Specific examples of the phosphate compounds represented by the general formula (5) are preferably monophosphate compounds such as triphenyl phosphate and tris(2,6-xylyl) phosphate, and phosphate oligomers mainly composed of resorcinol bis(2,6-xylyl) phosphate, phosphate oligomers mainly composed of 4,4-dihydroxybiphenyl bis(diphenyl phosphate), and phosphate oligomers mainly composed of bisphenol A bis(diphenyl phosphate). Among them, phosphate oligomers mainly composed of resorcinol bis(2,6-xylyl) diphosphate, phosphate oligomers mainly composed of 4,4-dihydroxybiphenyl bis(diphenyl phosphate), and phosphate oligomers mainly composed of bisphenol A bis(diphenyl phosphate) are preferred.

[0176] <Component D-3: Phosphazene compound>

[0177] The phosphazene compound used in the present invention does not contain a halogen atom and is not particularly limited as long as it is a compound having a phosphazene structure in the molecule. The phosphazene structure represented by the formula: -P(R 2 )=N-[wherein, R 2 The phosphazene is represented by the general formula (6) and (7).

[0178]

[0179] (In the general formulae (6) and (7), X1, X2, X3, and X4 represent hydrogen, a hydroxyl group, an amino group, or an organic group not containing a halogen atom. In addition, n represents an integer of 3 to 10.)

[0180] In the above general formulae (6) and (7), examples of the organic group not containing a halogen atom represented by X1, X2, X3, and X4 include alkoxy, phenyl, amino, and allyl groups. Among them, a cyclic phenoxyphosphazene represented by the following general formula (8) is preferred.

[0181]

[0182] [In the general formula (8), m represents an integer of 3 to 25. Ph represents a phenyl group.]

[0183] Examples of commercially available products of the phosphazene compound include SPS-100, SPR-100, SA-100, SPB-100, and SPB-100L (all manufactured by Otsuka Chemical Co., Ltd.), and FP-100 and FP-110 (all manufactured by Fushimi Pharmaceutical Co., Ltd.).

[0184] <Component D-4: Sulfonic acid metal salt>

[0185] The metal used in the sulfonic acid metal salt used in the present invention is preferably an alkali metal or an alkaline earth metal, and more preferably an alkali metal. Examples of the alkali metal include lithium, sodium, potassium, rubidium, and cesium, and examples of the alkaline earth metal include beryllium, magnesium, calcium, strontium, and barium, and lithium, sodium, and potassium are particularly preferred.

[0186] As the sulfonic acid used for the sulfonic acid metal salt used in the present invention, an organic sulfonic acid is preferred, and an aliphatic sulfonic acid or an aromatic sulfonic acid is more preferred.

[0187] The aliphatic sulfonic acid is preferably an alkylsulfonic acid, more preferably a fluoroalkylsulfonic acid in which a part or all of the alkyl groups are substituted with fluorine atoms, and most preferably a perfluoroalkylsulfonic acid in which all of the alkyl groups are substituted with fluorine atoms. Preferred examples of perfluoroalkylsulfonic acids include perfluoromethanesulfonic acid, perfluoroethanesulfonic acid, perfluoropropanesulfonic acid, perfluorobutanesulfonate, perfluoromethylbutanesulfonic acid, perfluorohexanesulfonic acid, perfluoroheptanesulfonic acid, and perfluorooctanesulfonic acid, and perfluoroalkylsulfonic acid having 1 to 8 carbon atoms is particularly preferred. These can be used alone or in combination of two or more.

[0188] Examples of the aromatic sulfonic acid include at least one acid selected from the group consisting of monomeric or polymeric sulfonic acids of aromatic sulfides, sulfonic acids of aromatic carboxylic acids and esters, monomeric or polymeric sulfonic acids of aromatic ethers, sulfonic acids of aromatic sulfonic esters, monomeric or polymeric aromatic sulfonic acids, monomeric or polymeric sulfonic acids of aromatic sulfones, sulfonic acids of aromatic ketones, heterocyclic sulfonic acids, sulfonic acids of aromatic sulfoxides, and condensates of aromatic sulfonic acids linked via methylene type bonds. These may be used alone or in combination of two or more.

[0189] <Component D-5: Silicone compound>

[0190] The organosilicon compound used in the present invention preferably has a highly active group, and preferred examples thereof include an alkoxy group or a Si-H group. The content ratio of the group is preferably in the range of 0.1 to 1.2 mol / 100 g, more preferably in the range of 0.12 to 1 mol / 100 g, and further preferably in the range of 0.15 to 0.6 mol / 100 g. The ratio is obtained by measuring the amount of hydrogen or alcohol produced per unit weight of the organosilicon compound by an alkali decomposition method.

[0191] The alkoxy group is preferably an alkoxy group having 1 to 4 carbon atoms, and a methoxy group is particularly preferred.

[0192] Generally speaking, the structure of an organosilicon compound is formed by arbitrarily combining the following four types of siloxane units. That is, M unit: (CH3)3SiO 1 / 2 、H(CH3)2SiO 1 / 2 、H2(CH3)SiO 1 / 2 、(CH3)2(CH2=CH)SiO 1 / 2 、(CH3)2(C6H5)SiO 1 / 2 、(CH3)(C6H5)(CH2=CH)SiO 1 / 2 Monofunctional siloxane units such as (CH3)2SiO, H(CH3)SiO, H2SiO, H(C6H5)SiO, (CH3)(CH2=CH)SiO, (C6H5)2SiO, etc.; T units: (CH3)SiO 3 / 2 、(C3H7)SiO 3 / 2 ,HSiO 3 / 2 、(CH2=CH)SiO 3 / 2 、(C6H5)SiO 3 / 2 Q unit: a tetrafunctional siloxane unit represented by SiO2.

[0193] The structure of the organosilicon compound used in the organosilicon flame retardant can be specifically represented by Dn, Tp, MmDn, MmTp, MmQq, MmDnTp, MmDnQq, MmTpQq, MmDnTpQq, DnTp, DnQq, and DnTpQq. Among them, the preferred structures of the organosilicon compound are MmDn, MmTp, MmDnTp, and MmDnQq, and the more preferred structure is MmDn or MmDnTp.

[0194] Here, the coefficients m, n, p, and q in the above-mentioned indicative formula are integers greater than 1 representing the degree of polymerization of each siloxane unit, and the sum of the coefficients in each indicative formula is the average degree of polymerization of the organosilicon compound. The average degree of polymerization is preferably in the range of 3 to 150, more preferably in the range of 3 to 80, further preferably in the range of 3 to 60, and particularly preferably in the range of 4 to 40. If it is in the above-mentioned preferred range, the flame retardancy is excellent. And as described below, the transparency and color tone are also excellent in the organosilicon compound containing a specified amount of aromatic groups. As a result, good reflected light can be obtained.

[0195] When any one of m, n, p and q is a value of 2 or more, the siloxane unit having the coefficient may be two or more siloxane units having different hydrogen atoms or organic residues bonded thereto.

[0196] The organosilicon compound may be straight-chain or branched. The organic residue bonded to the silicon atom is preferably an organic residue having 1 to 30 carbon atoms, more preferably 1 to 20 carbon atoms. Specifically, the organic residue includes alkyl groups such as methyl, ethyl, propyl, butyl, hexyl and decyl, cycloalkyl groups such as cyclohexyl, aryl groups such as phenyl, and aralkyl groups such as tolyl. Alkyl groups, alkenyl groups or aryl groups having 1 to 8 carbon atoms are further preferred. As the alkyl group, alkyl groups having 1 to 4 carbon atoms such as methyl, ethyl and propyl groups are particularly preferred.

[0197] In addition, the organosilicon compound used as the organosilicon flame retardant preferably contains an aromatic group. On the other hand, the silane compound and the siloxane compound used as the organic surface treatment agent of the titanium dioxide pigment can obtain a preferred effect when they do not contain an aromatic group, and in this respect, they are clearly different from the organosilicon flame retardant in their preferred form. A more preferred organosilicon flame retardant is an organosilicon compound containing an aromatic group in a ratio (aromatic group amount) of 10 to 70% by weight (more preferably 15 to 60% by weight).

[0198] <Ingredient E: Anti-drip agent>

[0199] As the anti-drip agent used as the E component in the present invention, a fluorine-containing polymer having fibril forming ability can be mentioned, and as the polymer, polytetrafluoroethylene, tetrafluoroethylene copolymers (e.g., tetrafluoroethylene / hexafluoropropylene copolymers, etc.), partially fluorinated polymers as shown in the communique of U.S. Patent No. 4379910, polycarbonate resins manufactured from fluorinated diphenol, etc. can be mentioned. Among them, polytetrafluoroethylene (hereinafter sometimes referred to as PTFE) is preferred.

[0200] The molecular weight of PTFE with fibril forming ability has extremely high molecular weight, and shows the trend that PTFE is bonded to each other and becomes fibrous by external effects such as shearing force. Its molecular weight is 1,000,000~10,000,000 with the number-average molecular weight tried to be achieved by standard specific gravity, and is preferably 2,000,000~9,000,000. Above-mentioned PTFE can also use the PTFE of aqueous dispersion form except solid shape. In addition, above-mentioned PTFE with fibril forming ability can also use the PTFE mixture of mixed form with other resin in order to improve the dispersibility in resin, and obtain good flame retardancy and mechanical properties.

[0201] As the commercially available product of the PTFE with fibril forming ability, for example, TEFLON (registered trademark) 6-J of Chemours-Mitsui Fluoroproducts Co., Ltd., Polyflon MPAFA500H and F-201 of Daikin Industries, Ltd., etc. can be enumerated. As the commercially available product of the aqueous dispersion of PTFE, Fluon D series made by Daikin Industries, Ltd., TEFLON (registered trademark) 31-JR of Chemours-Mitsui Fluoroproducts Co., Ltd., etc. can be enumerated as representative.

[0202] As a mixed form of PTFE, PTFE obtained by the following methods can be used: (1) a method of mixing an aqueous dispersion of PTFE with an aqueous dispersion or solution of an organic polymer and coprecipitating the mixture to obtain a coagulated mixture (methods described in Japanese Unexamined Patent Publication No. 60-258263, Japanese Unexamined Patent Publication No. 63-154744, etc.); (2) a method of mixing an aqueous dispersion of PTFE with dried organic polymer particles (method described in Japanese Unexamined Patent Publication No. 4-272957); (3) a method of uniformly mixing an aqueous dispersion of PTFE with a solution of organic polymer particles. (4) a method of polymerizing monomers forming an organic polymer in an aqueous dispersion of PTFE (a method described in Japanese Unexamined Patent Publication No. 06-220210 and Japanese Unexamined Patent Publication No. 08-188653); (5) a method of uniformly mixing an aqueous dispersion of PTFE with an organic polymer dispersion, and then polymerizing a vinyl monomer in the mixed dispersion to obtain a mixture (a method described in Japanese Unexamined Patent Publication No. 11-29679). Commercially available products of these mixed PTFEs include "METABLEN A3800" (trade name) and "METABLEN A3750" of Mitsubishi Chemical Corporation.

[0203] The proportion of PTFE in the mixed form is preferably 1 to 60% by weight, more preferably 5 to 55% by weight, based on 100% by weight of the PTFE mixture. When the proportion of PTFE is within the above range, good dispersibility of PTFE may be achieved.

[0204] As the styrene monomer of the organic polymer used in the polytetrafluoroethylene mixture, styrene which can be substituted by one or more groups selected from alkyl groups having 1 to 6 carbon atoms, alkoxy groups having 1 to 6 carbon atoms and halogens, such as o-methylstyrene, m-methylstyrene, p-methylstyrene, dimethylstyrene, ethylstyrene, p-tert-butylstyrene, methoxystyrene, fluorostyrene, monobromostyrene, dibromostyrene and tribromostyrene, vinylxylene and vinylnaphthalene can be exemplified, but it is not limited to these. The above styrene monomers can be used alone or in combination of two or more.

[0205] The acrylic monomer used in the organic polymer used in the polytetrafluoroethylene-based mixture of the present invention includes a (meth)acrylate derivative which may be substituted. Specifically, as the acrylic monomer, there can be exemplified (meth)acrylate derivatives which may be substituted with one or more groups selected from alkyl groups having 1 to 20 carbon atoms, cycloalkyl groups having 3 to 8 carbon atoms, aryl groups, and glycidyl groups, such as (meth)acrylonitrile, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, octyl (meth)acrylate, dodecyl (meth)acrylate, phenyl (meth)acrylate, benzyl (meth)acrylate, and glycidyl (meth)acrylate, maleimide which may be substituted with an alkyl group having 1 to 6 carbon atoms or an aryl group, such as maleimide, N-methyl-maleimide and N-phenyl-maleimide, maleic acid, fumaric acid, and itaconic acid, but are not limited thereto. The acrylic monomers can be used alone or in combination of two or more. Among these, (meth)acrylonitrile is preferred.

[0206] In addition, the coated branched PTFE can be used as an anti-drip agent in the present invention. The coated branched PTFE is a polytetrafluoroethylene mixture composed of branched polytetrafluoroethylene particles and an organic polymer, and has a coating layer composed of an organic polymer, preferably a polymer containing units from styrene monomers and / or units from acrylic monomers, on the outside of the branched polytetrafluoroethylene. The coating layer is formed on the surface of the branched polytetrafluoroethylene. In addition, the coating layer preferably contains a copolymer of styrene monomers and acrylic monomers.

[0207] The polytetrafluoroethylene contained in the coated branched PTFE is a branched polytetrafluoroethylene. When the polytetrafluoroethylene contained is not a branched polytetrafluoroethylene, the anti-drip effect is insufficient when a small amount of polytetrafluoroethylene is added. The branched polytetrafluoroethylene is in a particle form, preferably having a particle size of 0.1 to 0.6 μm, more preferably 0.3 to 0.5 μm, and further preferably 0.3 to 0.4 μm. When the particle size is less than 0.1 μm, the surface appearance of the molded article is excellent, but polytetrafluoroethylene having a particle size of less than 0.1 μm is not easily obtained commercially. In addition, when the particle size is greater than 0.6 μm, the surface appearance of the molded article sometimes deteriorates. The number average molecular weight of the polytetrafluoroethylene used in the present invention is preferably 1×10 4 ~1×10 7 , more preferably 2×10 6 ~9×10 6 Generally speaking, from the perspective of stability, high molecular weight polytetrafluoroethylene is more preferred. It can be used in the form of powder or dispersion.

[0208] The content of the branched polytetrafluoroethylene in the coated branched PTFE is preferably 20 to 60 parts by weight, more preferably 40 to 55 parts by weight, further preferably 47 to 53 parts by weight, particularly preferably 48 to 52 parts by weight, and most preferably 49 to 51 parts by weight, relative to 100 parts by weight of the total weight of the coated branched PTFE. When the ratio of the branched polytetrafluoroethylene is within the above range, good dispersibility of the branched polytetrafluoroethylene can sometimes be achieved.

[0209] Relative to 100 parts by weight of component A, the content of component E is preferably 0.05 to 3 parts by weight, more preferably 0.1 to 2 parts by weight, and further preferably 0.2 to 1.5 parts by weight. If it is larger than this range, it leads to rising costs, and sometimes extrusion processability becomes insufficient. On the other hand, if it is smaller than this range, sometimes flame retardancy is insufficient and tensile strength also decreases. It should be noted that the ratio of the above-mentioned component E represents the amount of the anti-drip agent by net weight, and in the case of mixed PTFE, it represents the amount of PTFE by net weight.

[0210] <Other ingredients>

[0211] The thermoplastic resin composition of the present invention may contain various fillers and other additives in addition to the component C, within the range not impairing the object of the present invention.

[0212] <Production of thermoplastic resin composition>

[0213] When manufacturing the thermoplastic resin composition of the present invention, any method may be adopted. For example, the following method may be mentioned: after fully mixing component A, component B and any other components using a premixing mechanism such as a V-type blender, a Henschel mixer, a mechanochemical device, an extrusion mixer, etc., the premix is ​​granulated using an extrusion granulator, a briquetting machine, etc. as needed, and then melt-kneading is performed using a melt-kneading machine represented by a vented twin-screw extruder, and then pelletized using a granulator.

[0214] In addition, there can be mentioned a method of independently supplying each component to a melt kneader represented by a vented twin-screw extruder; a method of premixing a part of each component and then supplying it to a melt kneader independently from the remaining components, etc. As a method of premixing a part of each component, for example, there can be mentioned a method of premixing components other than component A in advance and then mixing them into the thermoplastic resin of component A or directly supplying them to an extruder.

[0215] As a method for premixing, for example, the following method can be cited: when a substance having a powder form is included as component A, a part of the powder is blended with a formulated additive to produce a masterbatch of the additive diluted with the powder, and the masterbatch is used. In addition, a method of independently supplying a single component from the middle of a melt extruder can also be cited. It should be noted that when a liquid substance is included in the formulated component, the supply to the melt extruder can use a so-called liquid injection device or a liquid adding device.

[0216] As an extruder, it is preferred to use an extruder with an exhaust port that can degas the moisture in the raw material and the volatile gas produced by the melt-kneaded resin. It is preferably provided with a vacuum pump that is used to efficiently discharge the generated moisture and volatile gas from the exhaust port to the outside of the extruder. In addition, a screen cloth for removing foreign matter mixed into the extrusion raw material can also be provided in the area before the die head of the extruder, so as to remove foreign matter from the resin combination. As the screen cloth, metal mesh, screen changer (screen changer), sintered metal plate (disc filter, etc.) etc. can be cited.

[0217] Examples of the melt kneading machine include a twin-screw extruder, a Banbury mixer, a kneading roll, a single-screw extruder, and a multi-screw extruder having three or more screws.

[0218] For the resin extruded as described above, it can be directly cut for granulation, or the strand can be cut with a granulator after forming a strand for granulation. When it is necessary to reduce the influence of external dust, etc. during granulation, it is preferred to purify the environment around the extruder. In addition, in the manufacture of the above-mentioned particles, various methods proposed in the polycarbonate resin for optical discs can be used to appropriately narrow the shape distribution of the particles, reduce the amount of missed cuts, reduce the amount of fine powder generated during transportation or conveying, and reduce the bubbles (vacuum bubbles) generated inside the strands or particles. Through these formulations, it is possible to achieve high circulation of molding and reduce the proportion of defects such as silver streaks. In addition, the shape of the particles can be general shapes such as cylinders, square columns and spheres, and more preferably cylinders. The diameter of the cylinder is preferably 1 to 5 mm, more preferably 1.5 to 4 mm, and more preferably 2 to 3.3 mm. On the other hand, the length of the cylinder is preferably 1 to 30 mm, more preferably 2 to 5 mm, and more preferably 2.5 to 3.5 mm.

[0219] [Effects of the Invention]

[0220] The thermoplastic resin composition of the present invention is a thermoplastic resin composition that has little discoloration and strength reduction even under severe processing conditions, is excellent in recyclability, and is excellent in flame retardancy and rigidity. Therefore, it is useful in applications requiring thin-wall and light-weight molding conditions at high temperatures and in the case of recycling products, and has a great industrial effect.

[0221] The inventors of the present invention believe that the best mode of the present invention at present is a mode that combines the preferred ranges of the above-mentioned requirements, and representative examples thereof are described in the following embodiments. Of course, the present invention is not limited to these modes.

[0222] Example

[0223] The following examples are given for further explanation, but the present invention is not limited thereto. It should be noted that the following items were implemented as evaluations.

[0224] (i) Color change during retention

[0225] The pellets obtained from the compositions of the examples were dried at 100°C with a hot air dryer for 5 hours, and injection-molded 100 times (shots) at the temperature in the table using an injection molding machine [SG150U·SM IV manufactured by Sumitomo Heavy Industries, Ltd.] to obtain a 150 mm × 150 mm × 2 mm square plate. The operation of the molding machine was then interrupted to allow the resin to remain in the barrel. After 15 minutes, the square plate was molded again, and the color tone of the square plate before and after retention was measured using a colorimeter TC-1800MKII manufactured by Tokyo Denshoku, and the color difference (ΔE) before and after retention was calculated.

[0226] (ii) Strength retention during retention

[0227] The square plate used in "(i) Discoloration during retention" was used to perform a high-speed surface impact test, and the fracture energy of the square plate before and after retention was measured. The strength retention rate before and after retention was calculated by the following formula. It should be noted that the measurement was performed using Hydroshot HTM-1 manufactured by Shimadzu Corporation at 23°C and a test speed of 7 m / s.

[0228] Strength retention (%) = [fracture energy after retention / fracture energy before retention] × 100

[0229] (iii) Circularity

[0230] The square plates before retention used in "(i) Discoloration during retention" were placed horizontally outdoors in the Midori-ku area of ​​Chiba City for one year, and then crushed and reshaped into square plates. The color tone and fracture energy of the square plates before placement and the reshaped square plates were measured by the same methods as in "(i) Discoloration during retention" and "(ii) Strength retention during retention", and the color difference (ΔE) and strength retention of the two were measured.

[0231] (iv) Flame retardancy

[0232] The pellets obtained from the compositions of the examples were dried at 100°C for 5 hours using a hot air dryer, and continuously molded into UL test pieces at the temperature in the table using an injection molding machine [SG150U·SM IV manufactured by Sumitomo Heavy Industries, Ltd.]. A V test (vertical burning test) at a thickness of 1.5 mm was performed in accordance with UL94.

[0233] (v) Flexural modulus

[0234] The bending elastic modulus value was measured using the test piece before retention used in "(i) Discoloration during retention".

[0235] [Examples 1 to 40, Comparative Examples 1 to 11]

[0236] According to the following instructions, a resin composition composed of the mixing ratios in Tables 1 to 3 is prepared. It should be noted that the description is explained according to the symbols in the following tables. After the components of the proportions in the metering table are uniformly mixed using a tumbler, the mixture is put into an extruder to prepare the resin composition. The extruder uses a vent-type twin-screw extruder TEX-30XSST (fully meshed, co-rotating, double-threaded screw) manufactured by Nippon Steel Works, Ltd. It should be noted that the glass fiber, plate-shaped glass filler, and fibrous carbon filler in the inorganic filler are supplied from the second supply port, and the other components are supplied from the first supply port. The extrusion conditions are a discharge volume of 20 kg / h, a screw speed of 150 rpm, a vacuum degree of 3 kPa, and an extrusion temperature of the temperature in the table. The obtained pellets are molded into test pieces for evaluation using an injection molding machine by the above-mentioned method. The evaluation results are shown in Tables 1 to 3. It should be noted that the components represented by the symbols in Tables 1 to 3 are as follows.

[0237] (Component A: thermoplastic resin)

[0238] A-1-1: Aromatic polycarbonate resin (polycarbonate resin powder having a viscosity average molecular weight of 20,700 produced from bisphenol A and phosgene by a conventional method, Panlite L-1225WS (product name) manufactured by Teijin Limited)

[0239] A-1-2: Modified polycarbonate resin powder having a viscosity average molecular weight of 22,300 obtained by the following method

[0240] 4229 parts of 48% sodium hydroxide aqueous solution and 20000 parts of ion exchange water were placed in a reactor equipped with a thermometer, a stirrer and a reflux cooler, 2191 parts of 1,1-bis(4-hydroxy-3-methylphenyl)propane (hereinafter abbreviated as Bis-1), 1951 parts of bisphenol A and 8.3 parts of sodium dithionite were dissolved therein, and then 11620 parts of dichloromethane were added, and 2200 parts of phosgene were blown into the mixture at 15 to 25°C for about 60 minutes under stirring. After the blowing of phosgene was completed, 704 parts of 48% sodium hydroxide aqueous solution and 102 parts of p-tert-butylphenol were added, and stirring was resumed. After emulsification, 4.32 parts of triethylamine were added, and stirring was further performed at 28 to 33°C for 1 hour to terminate the reaction. After the reaction was completed, the product was washed with dichloromethane diluted water, and then washed with hydrochloric acid to make it acidic, and the washing was repeated until the conductivity of the aqueous phase was almost the same as that of the ion exchange water, thereby obtaining a dichloromethane solution of a polycarbonate resin. Next, the solution was passed through a filter with a mesh size of 0.3 μm and further added dropwise to warm water in a kneader with an isolation chamber having a foreign matter removal port in the bearing portion, and the polycarbonate resin was flaked while distilling off dichloromethane. The liquid-containing flakes were then crushed and dried to obtain powders.

[0241] A-1-3: polycarbonate-polydiorganosiloxane copolymer resin (viscosity average molecular weight 19800, PDMS content 4.2%, PDMS polymerization degree 37)

[0242] A-2: ABS resin (SANTAC AT-07 (trade name) manufactured by Japan A&L Co., Ltd., butadiene rubber component about 17.5% by weight, rubber weight average particle size 1.2 μm, manufactured by bulk polymerization)

[0243] A-3: Polyethylene terephthalate (TRN-8550FF (trade name) manufactured by Teijin Co., Ltd.)

[0244] A-4: AS resin (LITACABS-207 (trade name) manufactured by Japan A&L Co., Ltd.)

[0245] A-5: PS resin (GP-110 (trade name) manufactured by IRPC Public Company Limited)

[0246] A-6: AAS resin (777K (trade name) manufactured by INEOS)

[0247] (Component B: phosphonate)

[0248] B-1: triethyl phosphonoacetate (JC-224 (trade name) manufactured by Johoku Chemical Industry Co., Ltd., acid value 0.08 mgKOH / g)

[0249] B-2 (Comparative Example): triethyl phosphonoacetate (manufactured by Solvay, acid value 0.39 mgKOH / g)

[0250] B-3: triethyl phosphonoacetate (mixture of B-1 and B-2 (weight ratio 1:1), acid value 0.23 mgKOH / g)

[0251] (Component C: Inorganic filler)

[0252] C-1: Glass fiber (3PE937 (product name) manufactured by Nitto Bosho Co., Ltd.)

[0253] C-2: Glass flake (MEG160FYX (product name) manufactured by Nippon Sheet Glass Co., Ltd.)

[0254] C-3: Carbon fiber (HT C493 (product name) manufactured by Teijin Limited)

[0255] C-4: Non-fibrous carbon filler (EN-250HT (product name) manufactured by Nishimura Black Lead Co., Ltd.)

[0256] C-5: Talc (Pyrophyllite TK-RC (product name) manufactured by Shokosan Mining Co., Ltd.)

[0257] (Component D: flame retardant)

[0258] D-1: Tetrabromobisphenol A carbonate oligomer (FG-7000 (product name) manufactured by Teijin Limited)

[0259] D-2: Phosphate ester containing resorcinol [bis(2,6-dimethylphenyl) phosphate] as the main component (PX-200 (trade name) manufactured by Daihachi Chemical Industry Co., Ltd.)

[0260] D-3: Cyclic phenoxyphosphazene (FP-110 (trade name) manufactured by Fushimi Pharmaceutical Co., Ltd.)

[0261] D-4: Potassium perfluorobutanesulfonate (EFTOP KSBF (product name) manufactured by Mitsubishi Materials Co., Ltd.)

[0262] D-5: an organosiloxane flame retardant containing a Si—H group, a methyl group, and a phenyl group (X-40-2600J (trade name) manufactured by Shin-Etsu Chemical Co., Ltd.)

[0263] (Ingredient E: anti-drip agent)

[0264] E-1: Polytetrafluoroethylene (Polyflon MPFA500B (trade name) manufactured by Daikin Industries, Ltd.)

[0265]

[0266]

[0267]

Claims

1. A thermoplastic resin composition comprising 0.001 to 1 part by weight of (B) a phosphonate having an acid value of 0.01 to 0.30 mgKOH / g, as component B, based on 100 parts by weight of (A) a thermoplastic resin, as component A.

2. The thermoplastic resin composition according to claim 1, wherein The (C) inorganic filler, ie, component C, is contained in an amount of 1 to 150 parts by weight based on 100 parts by weight of component A.

3. The thermoplastic resin composition according to claim 1 or 2, wherein The (D) flame retardant, that is, the component D, is contained in an amount of 0.01 to 25 parts by weight based on 100 parts by weight of the component A.

4. The thermoplastic resin composition according to claim 2 or 3, wherein The (E) anti-drip agent, that is, component E, is contained in an amount of 0.05 to 3 parts by weight based on 100 parts by weight of component A.

5. The thermoplastic resin composition according to any one of claims 1 to 4, wherein Component A is at least one thermoplastic resin selected from the group consisting of (A-1) polycarbonate resin (component A-1), (A-2) ABS resin (component A-2), (A-3) polyester resin (component A-3), (A-4) AS resin (component A-4), (A-5) PS resin (component A-5), and (A-6) AAS resin (component A-6).

6. The thermoplastic resin composition according to any one of claims 1 to 4, wherein Component A is at least one thermoplastic resin selected from the group consisting of (A-1) polycarbonate resin (component A-1), (A-2) ABS resin (component A-2), and (A-3) polyester resin (component A-3).

7. The thermoplastic resin composition according to claim 5 or 6, wherein The content of the component A-1 is 40 to 100 parts by weight in 100 parts by weight of the component A.

8. The thermoplastic resin composition according to any one of claims 1 to 7, wherein Component B is triethyl phosphonoacetate.

9. The thermoplastic resin composition according to claim 2, wherein Component C is at least one inorganic filler selected from the group consisting of (C-1) glass fiber, i.e. component C-1; (C-2) plate-shaped glass filler, i.e. component C-2; (C-3) fibrous carbon filler, i.e. component C-3; (C-4) non-fibrous carbon filler, i.e. component C-4; and (C-5) silicate mineral, i.e. component C-5.

10. The thermoplastic resin composition according to claim 3, wherein The component D is at least one flame retardant selected from the group consisting of (D-1) a halogenated carbonate compound (component D-1), (D-2) a phosphate ester compound (component D-2), (D-3) a phosphazene compound (component D-3), (D-4) a sulfonic acid metal salt (component D-4), and (D-5) an organosilicon compound (component D-5).

11. The thermoplastic resin composition according to claim 4, wherein Component E is polytetrafluoroethylene.

12. A molded article comprising the thermoplastic resin composition according to any one of claims 1 to 11.